MICRO/NANOPARTÍCULAS POLIMÉRICAS E BIODEGRADÁVEIS DE MESOCARPO DE BABAÇU: AÇÃO IMUNOMODULADORA NA POLARIZAÇÃO DE MACRÓFAGOS E EFEITO ANTI-LEISHMANIA - SILVA, Mayara Cristina Pinto da (2017)
There is an increasing interest to find new products with therapeutic potential to the treatment of leishmaniasis, due the high toxicity and resistance of the majority of available treatments. Our aim was to formulate, characterise and evaluate the antiLeishmania amazonensis activity of babassu loaded poly(lactic-co-glycolic acid) – PLGA microparticles. The PLGA microparticles were loaded with the aqueous extract of babassu mesocarp (MMP) and evaluated for size, zeta potential, drug content, encapsulation efficiency in comparison to unloaded microparticles (CMP). The antiLeishmania effect was evaluated to promastigotes forms or to amastigotes in Balb/c macrophage cells infected with Leishmania amazonensis. Following macrophage treatment with MMP the percent of infected cells was determined by Giemsa staining and compared with cells treated with CMP or with free babassu extract (MESO). To find the potential mechanisms of the activity of MMPs, TNF -α, IL-6, IL-10, hydrogen peroxide, arginase and accumulated nitrite in the culture supernatants of the treated and untreated cells were also measured by ELISA, and by colorimetric assays, respectivelly. The size range of the microparticles was between 3 and 6,4 μm with an average zeta potential of −25 mV and encapsulation efficiency of 45%. The antiLeishmania activity of babassu-loaded microparticles was 10-fold higher than MESO. MMP showed an overall bioavailability and hence were more effective in eliminating intracellular parasites than the other formulations. Babassu microparticles also reduced the ex vivo parasite infectivity and this effect seems to be directly related to a polarization of macrophages to the M1 phenotype with an increased production of nitric oxide, hydrogen peroxide and TNF-α. Interestingly, this overexpression of TNF-α didn’t impair cell viability, suggesting the anti-apoptotic effects of the MMP in infected macrophages. These findings indicate that babassu load microparticles may be useful for targeting for new drugs, due to the immunomodulatory effects of polarization to M1 macrophages, infected with L. amazonensis, and further provide motivations for future studies on human cels in vitro and in animal models of leishmaniasis in vivo.